2014
DOI: 10.1038/srep05325
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of full-color InGaN-based light-emitting diodes on amorphous substrates by pulsed sputtering

Abstract: InGaN-based light-emitting diodes (LEDs) have been widely accepted as highly efficient light sources capable of replacing incandescent bulbs. However, applications of InGaN LEDs are limited to small devices because their fabrication process involves expensive epitaxial growth of InGaN by metalorganic vapor phase epitaxy on single-crystal wafers. If we can utilize a low-cost epitaxial growth process, such as sputtering on large-area substrates, we can fabricate large-area InGaN light-emitting displays. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 23 publications
0
102
0
Order By: Relevance
“…We have demonstrated that the growth mechanisms of PSD are inherently different from those behind the MOCVD growth, enabling the growth of high-quality nitride films at considerably lower growth temperatures owing to the enhanced surface migration of adatoms on the growth surfaces. [11][12][13][14][15][16][17] These features are also expected to facilitate the growth of high-quality N-polar nitride films because surface roughening in N-polar growth is probably caused by the insufficient surface migration of growth precursors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the growth mechanisms of PSD are inherently different from those behind the MOCVD growth, enabling the growth of high-quality nitride films at considerably lower growth temperatures owing to the enhanced surface migration of adatoms on the growth surfaces. [11][12][13][14][15][16][17] These features are also expected to facilitate the growth of high-quality N-polar nitride films because surface roughening in N-polar growth is probably caused by the insufficient surface migration of growth precursors.…”
mentioning
confidence: 99%
“…11 In fact, high-quality n-type and p-type GaN with room-temperature (RT) carrier mobilities of 1008 cm 2 V 1 s 1 and 34 cm 2 V 1 s 1 , respectively, 12 have already been prepared, and various devices such as light-emitting diodes (LEDs), 13,14 solar cells, high-electron mobility transistors, 15 and metal-insulator semiconductor field-effect transistors 16 were fabricated via PSD. The PSD growth mechanism involves the enhanced surface migration of film precursors from the pulsed-supplied group-III metals.…”
mentioning
confidence: 99%
“…The use of PSD enables the growth of device-quality group-iii nitrides at much lower temperatures than those used in the conventional MOCVD process. [6][7][8][9][10][11] PSD is suitable for growing heavily impurity-doped GaN because of its highly nonequilibrium nature. In fact, heavily Si-doped GaN prepared by PSD exhibited a RT electron 13 These achievements in the growth of highly conductive, heavily doped n-type GaN provide a good opportunity for systematically investigating the transport properties of degenerate GaN.…”
mentioning
confidence: 99%
“…8,10-13 Such low-temperature growth enables epitaxial growth of GaN and AlN films even on chemically vulnerable substrates such as metal because the interfacial reactions between nitride films and substrates are suppressed. [14][15][16][17] In this study, we have investigated the feasibility of epitaxial growth of GaN films on matched Hf (0001) substrates with small lattice mismatches using the low-temperature (LT) growth technique involving PXD.…”
mentioning
confidence: 99%